Dislocating the Body and Transcending the Imperial Eye (I): The role of Abaphantsi, through iiZangoma, as pioneers for transformative research methodologies and organic intellectualism - Zwane, Li'Tsoanelo (Department of Sociology, 2022)
In this study, I establish myself as both researcher and respondent and I use the literal and figurative interpretations of the word ‘body' to discuss how canonical epistemological paradigms, through their construction of indigenous knowledge systems, construct African bodies and how this impacts knowledge and research methods. I discuss how the corporeal bodies of Sangomas have been constructed, particularly through problematic research approaches which focus on observations of the corporeal body. Critical here, is how the imperial gaze is unrelenting in its deconstruction and reconstruction of African bodies. By engaging with the cosmology of Sangomas and their interaction with ancestors, I discuss the ineptitude of western-centric hegemonic research approaches in providing substantial responses to the variety of social phenomena with which the Social Sciences grapple. I focus on Sangoma practices of inhlolo (divination), ukuphupha (dreams and dream analysis) and the valorization of umbilini (intuition) as useful tools for the reimagination of research methodologies which have the power to transcend the corporeal lens with which canonical research approaches have become synonymous. Critical to the cosmology of Sangomas is community and the communal production and sharing of knowledge which I propose is a useful framework for transcending the individualistic researcherfocused approach which dominates Social Science research. Through an engagement with the fallaciousness of bifurcated knowledge systems, I argue that it is untruthful to assume that indigenous knowledge systems and western knowledge systems do not interact with each other or have never interacted with each other in the past. I recommend an approach to research which invites an integration of various knowledge systems and diverse ways of knowing. Furthermore, I propose, through a discourse analysis on my reflexive practice as a Sangoma, the concept of Ubungoma (as praxis) with its related theoretical and methodical approaches to decolonising the knowledge archive through ukuphupha as a pathway to insights, inhlolo as a quest for knowledge and ukuphahla as a decolonial research methodology.